Tectonophysical approach to the analysis of geological and geophysical data on gas-condensate deposits with the complex platform cover - K. Zh. Seminsky; V. A. Sankov; V. V. Ogibenin; Yu. P. Burzunova; A. I. Miroshnichenko; E. A. Gorbunova; I. V. Gorlov; A. S. Smirnov; A. G. Vakhromeev; I. V. Buddo (Геодинамика и тектонофизика)
The article presents the results of the tectonophysical approach to the analysis of stress fields and the structure of gas–condensate deposits with the complex platform cover. The discussed case is the Kovykta license area (LA) in Eastern Siberia, Russia. In the upper part of the cross section, the network of fault zones was identified from the relief lineaments and structural data. The dynamic conditions for faulting (compression, extension, and strike-slip) were reconstructed by the paragenetic analysis. The state of crustal stresses in the study area was studied by tectonophysical modeling using gelatin as an optically active material. The applied method was successful in distinguishing between the zones of faults in the platform cover, which differ in the degree of their activity in the specified stress fields. The lower part of the cross section in the NE segment of the Kovykta LA is considered as an example of the tectonophysical interpretation of the electrical and seismic survey data in order to identify the fault zones and reconstruct the corresponding stress fields. Based on the synthesis of the analyzed data, it is revealed that the deposits like the Kovykta gas condensate field (GCF) show the zone-block structure of the platform cover formed under the influence of several stress fields closely associated with the stages of tectogenesis in the adjacent mobile belts. The next objective is to enhance the tectonophysical approach in order to develop a hierarchical model of the GCF zone-block structure, which details need to be known for improving the prediction of sites with the complicated stress-strain state of rocks and mitigating the risks associated with drilling exploration and production wells.